The Bioaccumulation Of Heavy Metal Lead In Two Mangrove Species (Rhizophora apiculata and Aviicennia alba) by The Hydroponics Culture. - Sari, Irna; Din, Zubir; Gong, Wooi Khoon (USM, 2004)
The bioaccumulation of lead (Pb) at varying salinities by two species of mangrove, Avicennia alba and Rhizophora apiculata was studied under hydroponic cultivation.